1990
DOI: 10.1182/blood.v75.4.1017.bloodjournal7541017
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of corticosteroid resistant acute graft-versus-host disease by in vivo administration of anti-interleukin-2 receptor monoclonal antibody (B-B10) [see comments]

Abstract: In a multicenter pilot study, 32 patients showing steroid-resistant acute graft-versus-host disease (GVHD) were treated by in vivo administration of anti-interleukin-2 (IL-2) receptor monoclonal antibody (MoAb B-B10). Twenty-three patients received marrow from HLA- matched related donors, four from matched unrelated donors and five from partially matched related donors. The overall grade of GVHD was II in 16 patients, III in two, and IV in five. Five milligrams of B-B10 MoAb was infused in bolus daily for 10 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…There is no evidence that steroids alone are effective in this condition (17,(19)(20)(21). Anti-CD25 monoclonal antibodies have not, to our knowledge, been used for GVHD following solid organ transplantation, although they have been employed successfully for GVHD after bone marrow transplantation (9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no evidence that steroids alone are effective in this condition (17,(19)(20)(21). Anti-CD25 monoclonal antibodies have not, to our knowledge, been used for GVHD following solid organ transplantation, although they have been employed successfully for GVHD after bone marrow transplantation (9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…IL-2Ra is found on nearly all activated cytotoxic T cells, but not on resting T cells, enabling the development of more specific immunosuppression largely selective for activated T cells such as anti-CD25 antibody (6)(7)(8). These compounds have been used for acute GVHD following bone-marrow transplantation, with favorable outcome (9)(10)(11)(12). Our previous management of GVHD after orthotopic liver transplantation has employed increased doses of conventional immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have provided similar results with this approach when used as a therapy for GVHD nonresponsive to first-line therapy. The improvement in severity was about 40% (22)(23)(24)(25). However, this rate was no better than conventional second-line therapy (26), and may be due to the fact that memory T cells tend to lose IL-2Ra expression.…”
Section: Anti-il-2ra Mabmentioning
confidence: 99%
“…In mice, anti-CD3e-RTA administered in vivo has also eliminated CD3* cells responsible for marrow graft rejection, resulting in an overall promotion of longterm BM engraftment (38). Despite these and other reasons for targeting the CD3 complex, studies indicated that the in vivo use of anti-CD3E IT can be complicated by the fact that anti-CD3e tiiAb is mitogenic for T cells by the cross-linking of TCR/CD3 complexes when the Fc region of the IT is bound by Fc receptors on other ceils (20)(21)(22)(38)(39)(40). The subsequent precipitous release of inflammatory cytokines by IT-activated T cells caused a high mortahty rate.…”
mentioning
confidence: 99%
“…Based on these pathophysiological concepts, techniques for the prevention of acute GvHD have been developed using total or selective T-cell depletion of the graft. Also, trials of in vivo therapy of acute GvHD with the use of monoclonal anti-T cell or anti-IL-2 receptor antibodies have been carried out in an attempt to control the effector cell population {Volk et al 1986, Ferrara et al 1986, Waldman 1988, Herve et al 1990b). Yet, although T lymphocytes and IL-2 play a major role, other effector cells or cytokines also play important roles in GvHD.…”
Section: Anti-il2 Receptor Antibody In Acute Graft-versus-host Diseasementioning
confidence: 99%